Object Relational Mapping Framework Performance Impact (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In a world where frameworks play a key role in software applications, people tend to forget about the impact different frameworks can have on different software applications. This paper will look into the impact of different object-relational mapping frameworks on relational query performance. The objective is to give an average performance impact based on a wide variety of object-relational mapping frameworks. Results are gathered from experiments using 8 different frameworks for 4 different programming languages. The languages considered in this paper are Java, C#, Python and PHP. First, self-defined research questions are answered using literature research. These questions provide background information about the topic of object-relational object-relational frameworks. Secondly, the setup used for conducting the experiments covered in this paper is discussed. Finally, it concludes by showing the performance impact of the discussed object-relational mapping frameworks.